A Utilization Of Oil Palm Empty Fruit Bunch Biomass As An Alternative Fuel For Steam Power Plants - Wageman A. Naiborhu; Meijar Dwi Putra; Alfi S. B. Siahaan; Muhammad D. M. Lumban Tobing; Solly Aryza (INFOKUM, 2025)
The utilization of empty palm fruit bunches (EPFB) biomass as an alternative fuel for Steam Power Plants (PLTU) is a promising solution to reduce dependence on fossil fuels while increasing the utilization of palm oil industry waste. EPFB is a solid waste generated from the palm oil extraction process and has a high carbon content, making it a viable renewable energy source. This study aims to analyze the energy potential derived from the combustion of EPFB and the energy conversion efficiency in a PLTU system. The methodology includes the analysis of fuel characteristics, such as calorific value, moisture content, ash content, and combustion efficiency, compared to coal as a conventional fuel. Additionally, the study evaluates the environmental impact of utilizing EPFB as an alternative fuel, especially in terms of carbon emissions and energy efficiency. The results indicate that EPFB has an average calorific value of 15-18 MJ/kg, which is sufficient for use as fuel in co-firing systems with coal in PLTU. Using EPFB as an alternative fuel can also reduce CO₂ emissions by up to 30%compared to pure coal combustion. Economically, the utilization of EPFB can lower operational costs and support sustainable energy policies in Indonesia. Thus, the utilization of EPFB biomass in PLTU can provide an efficient and environmentally friendly renewable energy solution. Further implementation requires optimization of combustion technology and policy studies to support sustainable biomass use in power generation.